Milk quality as a funcion of temperature-cycled, reduced-fat milk stored in various size containers - Julstron, L.F.; Schmidt, Karen A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Packaged, reduced-fat milk was subjected to a 20 min/day temperature cycle during a 7-day refrigeration period to determine the ef-fect on milk quality. Temperature cycling did not affect the compositional or microbial counts in reduced-fat milk stored in various package sizes. Analysis of headspace com-pounds during the 7 days of storage, however, showed that benzaldehyde, 2-butanone, 2-heptanone, hexanal, and octanal concentra-tions significantly changed, indicating that milk flavor was altered. Concentration of heptanal, a compound associated with lipid oxidation, was higher in milk packaged in half-gallon and 1-gallon containers, compared
Dairy Research, 2006 is known as Dairy Day, 2006
Keywords: Dairy; Milk flavor; Packaging size; Temperature cycling